Exploring The Link Between the Entrepreneur, The Start-Up, And the Perceived Success in The Covid-19 Pandemic Era: Is There a Clear Connection? - Marina LOVRINCEVIC (Communications of International Proceedings, 2022)
This paper aims at investigating the relationship between characteristics of an entrepreneur, startup characteristics and the perceived success of startup companies, especially changes in the perception of success related to COVID-19 pandemic. Primary data were collected using an online survey questionnaire and were analysed using Mann-Whitney U test and Kruskal-Wallis test. The final research sample consisted of 61 startups and the results showed that no straightforward and consistent relationship between the characteristics of entrepreneur, the characteristics of startup, and the perception of overall startup success is evident. The contribution of this research should be situated with respect to identification of key factors contributing startup’s success and providing an insight into the startup community in Croatia, thus contributing to a scarce empirical literature on the topic available. Additionally, COVID-19 pandemic effects were included in the research design to capture potentially destructive outcomes since startup companies are particularly sensitive to disruptions and crisis. Limitations of the research include sample size and subjective assessment of the success factors, so recommendations for future research include repeating the research on a larger sample, covering the international level and widening a set of key-performance indicators that can be assessed at a higher level of rigour with objective metrics.
Keywords: COVID-19 pandemic; entrepreneurship; startup; success.